Fecal microbiome differs between patients with systemic sclerosis with and without small intestinal bacterial overgrowth. Issue 3 (October 2021) - Levin, Daniel; De Palma, Giada; Zou, Hannah; Bazzaz, Ava Hadi Zadeh; Verdu, Elena; Baker, Barbara; Pinto-Sanchez, Maria Ines; Khalidi, Nader; Larché, Maggie J; Beattie, Karen A.; Bercik, Premysl
Introduction: Gastrointestinal manifestations of systemic sclerosis affect up to 90% of patients, with symptoms including diarrhea and constipation. Small intestinal bacterial overgrowth is a condition associated with increased numbers of pathogenic bacteria in the small bowel. While currently unknown, it has been suggested that dysregulation of the fecal microbiota may play a role in the development of systemic sclerosis and small intestinal bacterial overgrowth. Objectives: Our study aimed to describe the fecal microbiota of patients with systemic sclerosis and compare it between those with and without a diagnosis of small intestinal bacterial overgrowth. We also compared the fecal microbiota of systemic sclerosis patients with that of healthy controls to understand the association between particular bacterial taxa and clinical gastrointestinal manifestations of systemic sclerosis. Methods: A total of 29 patients with systemic sclerosis underwent breath testing to assess for small intestinal bacterial overgrowth, provided stool samples to determine taxonomic assignments, and completed the University of California Los Angeles Scleroderma Clinical Trial Consortium Gastrointestinal Tract 2.0, which details symptoms and quality-of-life factors. Stool samples were compared between systemic sclerosis patients with and without small intestinal bacterial overgrowth, and between patients with systemic sclerosis and a healthy control cohort (n = 20), aged 18–80 years. Results: Fecal microbiome analyses demonstrated differences between systemic sclerosis patients with and without small intestinal bacterial overgrowth and differences in the diversity of species between healthy controls and patients with systemic sclerosis. Trends were also observed in anticentromere antibody systemic sclerosis patients, including higher Alistipies indistincus spp. levels associated with increased methane levels of breath gas testing and higher Slakia spp. levels associated with increased rates of fecal soiling. Conclusions: Our results suggest that changes to the fecal microbiome occur in patients with small intestinal bacterial overgrowth and systemic sclerosis when compared to healthy controls. As a cross-sectional study, the potential pathophysiologic role of an altered microbiome in the development of systemic sclerosis was not considered and hence needs to be further investigated.